2020
DOI: 10.3390/app10197002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Antioxidant Activities of Mixtures of Melastomataceae Leaves Species (M. malabathricum Linn Smith, M. decemfidum, and M. hirta) Using a Simplex Centroid Design and Their Anti-Collagenase and Elastase Properties

Abstract: In this study, a simplex-centroid mixture design (SCMD) approach was used to select the optimal proportions of three different Melastomataceae leaves species (M. malabathricum, M. decemfidum, and M. hirta) extracts to determine the optimum antioxidant activities of total phenolic compound (TPC) and ABTS (2, 2′-azino-bis (ethylbenzthiazoline-6-sulfonic acid)) radical-scavenging activities. Twelve experimental designs were set up, consisting of points that were equally weighted mixtures of 0 to 1 components, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Coumarin compound and its derivatives, such as 4-methyl chromen-2-one, have antioxidant activity because a stable quinoid structure is formed when hydrogen is added (Yasameen et al, 2017). This result is in line with the research of Bubols et al (2013), which states that, in the presence of a benzopyrone ring, flavonoids and coumarins are known to be potential sources of exogenous antioxidants. Another study reported that polyphenols can protect cell constituents damaged by oxidative stress because these compounds serve as potent free radical scavengers (Zaha et al, 2018).…”
Section: Phytochemical Analysis Using Gc-ms and Lc-ms/ms Fruit Extrac...supporting
confidence: 91%
See 3 more Smart Citations
“…Coumarin compound and its derivatives, such as 4-methyl chromen-2-one, have antioxidant activity because a stable quinoid structure is formed when hydrogen is added (Yasameen et al, 2017). This result is in line with the research of Bubols et al (2013), which states that, in the presence of a benzopyrone ring, flavonoids and coumarins are known to be potential sources of exogenous antioxidants. Another study reported that polyphenols can protect cell constituents damaged by oxidative stress because these compounds serve as potent free radical scavengers (Zaha et al, 2018).…”
Section: Phytochemical Analysis Using Gc-ms and Lc-ms/ms Fruit Extrac...supporting
confidence: 91%
“…The ferric reducing antioxidant power (FRAP) method for antioxidant activity determination was used on the basis of Benzie and Devaki (2017). Ten microliters of dried cardamom fruit extract and 300 μl of FRAP reagent were added to a 96well microplate (Costar, USA).…”
Section: Determination Of Iron-reducing Antioxidant Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…(kaempferol) [ 53 ], Osmbeckia parvifolia , Arnbeckia parvifolia , Medinilla septentrionalis (W.W.Sm.) H.L.Li [ 54 ], Melastoma malabathricum L., and M. hirta [ 55 ].…”
Section: Resultsunclassified